2022
DOI: 10.3390/antibiotics11050690
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of National Action Plan (NAP) on Antimicrobial Resistance (AMR) in Bangladesh: Challenges and Lessons Learned from a Cross-Sectional Qualitative Study

Abstract: This study explored the current situation of the National Action Plan (NAP) on Antimicrobial Resistance (AMR) implementation in Bangladesh and examined how different sectors (human, animal, and environment) addressed the AMR problem in policy and practice, as well as associated challenges and barriers to identifying policy lessons and practices. Informed by a rapid review of the available literature and following the World Health Organization (WHO) AMR situation analysis framework, a guideline was developed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…Antimicrobial resistance (AMR) is a worldwide threat to human health and progress. To attain the Sustainable Development Goals (SDGs), urgent multi-sectoral action is required [ 1 ]. Nanotechnology is becoming more widely used in medicine; thus, it is not surprising to find these technologies being used to combat the threat of antibiotic resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial resistance (AMR) is a worldwide threat to human health and progress. To attain the Sustainable Development Goals (SDGs), urgent multi-sectoral action is required [ 1 ]. Nanotechnology is becoming more widely used in medicine; thus, it is not surprising to find these technologies being used to combat the threat of antibiotic resistance.…”
Section: Introductionmentioning
confidence: 99%
“…This has been shown to be an issue for AMR strategies in general, with global AMR commitments from 2015 to 2021 remaining heavily focused on research, surveillance, and stewardship rather than the more upstream, preventative measures outlined in the 2015 AMR Global Action Plan . This further speaks to the need for AMR-sensitive approaches and the integration of AMR into wider sustainable development strategies. A recent study evaluating the implementation of the Bangladesh AMR NAP reported a lack of activities targeting AMR in the environmental sector, a shortage of a dedicated and trained workforce, and insufficient funding . Integrating AMR into wider sustainable development policies may also therefore prove to expedite NAP implementation from an efficiency perspective, through making use of existing funding, resources, and activities targeting the wider sustainable development goals.…”
Section: Resultsmentioning
confidence: 99%
“…5−7 A recent study evaluating the implementation of the Bangladesh AMR NAP reported a lack of activities targeting AMR in the environmental sector, a shortage of a dedicated and trained workforce, and insufficient funding. 73 Integrating AMR into wider sustainable development policies may also therefore prove to expedite NAP implementation from an efficiency perspective, through making use of existing funding, resources, and activities targeting the wider sustainable development goals. Since its development in the 1990s, the DPSIR framework has been applied to a very wide variety of issues and contexts, as both a conceptual and analytical tool.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“… 127 Additionally, inter-sectoral coordination with a “health in all” approach, and equitable distribution of resources for health and development are essential achieving UHC in face of the challenges of economic inequities, global uncertainty, antimicrobial resistance, and climate change. 75 , 128 In India, campaigns like “Eat right India”, “Fit India”, “Poshan Abhiyan”, integration of digital health technologies through “Ayushman Bharat Digital Mission” and launch of “National Programme on Climate Change & Human Health” provide an opportunity for inter-sectoral coordination.…”
Section: Methodsmentioning
confidence: 99%